Adolph Hummel: Music Publisher in Eighteenth-Century London. - Simlett-Moss, Joyce (Royal Musical Association Research Chronicle, 2021)
Adolph Hummel, from Hesse, established in Soho a music publishing business that lasted 12 years (1760–1772). His publishing strategy differed in several ways from that commonly adopted by London publishers: he published only foreign-born (mostly German or Italian) composers; he did not issue vocal music; and, while taking the common routes of advertising his publications by notices in contemporary newspapers and listing issues in the imprints to title pages, he was highly unusual in that he produced no catalogue. He was also unusual in obtaining a royal licence to protect his copyright. He was the first publisher in London to issue a string quartet, and possibly the first to add violin accompaniments to already-published solo harpsichord sonatas to create accompanied sonatas. He was probably related to the Hummel music publishing brothers of the Netherlands. Personal information about him is hard to come by, but we know that Frau Anna Maria Mozart was godmother to his youngest child; he was a particular friend of J. C. Bach; he was prosecuted, for an undisclosed reason, by the musician Rudolf Straube; and he was the founder of three generations of the musical 'English Hummells'. The final part of this article comprises a detailed catalogue of Hummel's publications.